The concept fury in Ukrainian media: Semiotic and cognitive potential - Ievgeniia Bondarenko (ELAD-SILDA)
This article examines the semiotic and cognitive dimensions of the concept fury, which has recently gained significant prominence in Ukrainian war-related media. The analysis positions fury as a key element of the Ukrainian construal of the world, as it fulfils the criteria of nation-building concept. The dual nature of the concept Fury necessitates the use of both semiotic and cognitive approaches in its study. From a semiotic perspective, the concept is explored through the Peircean framework, where it is analyzed as an icon, an index, and a symbol, with particular attention given to the distinct affordances of each and their hybrids. As a lexical concept, verbalized by the Ukrainian word лють (fury), it is initially viewed as a sign with significant potential for functioning as both an icon and a symbol. Furthermore, the lexical concept fury is investigated through the frameworks of the Lexical Concept and Cognitive Model (LCCM) Theory and the Extended Metaphor Theory. A corpus-based study of the Ukrainian lexical concept fury reveals its extensive potential as both a semiotic unit and a cognitive construal of metonymy and metaphor. The article presents the most frequent affordances of fury as a sign and a symbol, as well as its most common uses in metonymy and metaphor. The metaphorical scope of fury is also modelled with typical source domains identified.